Pengaruh Manajemen Rantai Pasokan Terhadap Keunggulan Kompetitif Dan Kinerja Perusahaan (Studi pada Usaha Kecil dan Menengah di Kabupaten Bantul) - Ilmiyati, Apriliana; Munawaroh, Munjiati (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to find about the impact of supply chain management on competitive advantage and organizational performance, and analyze the impact of supply chain management on organizational performance through competitive advantage as intervening. This research was conducted on Small and Medium Enterprises (SMEs) in Bantul with a population of 85 SMEs. Methods of data collection using questonaires distributed to the owner or manager of SMEs in Bantulwich has been registered on the SMEs Database Directory in Daerah Istimewa Yogyakarta of 2014. The analysis tool used in this study was multiple regression and simple regression which used SPSS software version 15.The result show the supply chain management have significant effect on competitive advantage and organizational performance, and competitive advantage have a significant effect on organizational performance. Competitive advantage be able to mediate impact of supply chain management on organizational performance.